Introduction to Events and Objects in Perception, Language, and Communication - Jeffrey M. Zacks (Baltic International Yearbook of Cognition, Logic and Communication, 2019)
This volume contains a selection of the papers presented at the 13th International Symposium on Cognition, Logic and Communication which took place in Riga, at the University of Latvia on December 8-9 2018.